USE OF CONSUMER DATA FOR BEHAVIOURAL ADVERTISING WITHIN MARKETPLACE PLATFORMS - Fabrício Germano Alves; da Mata Rodrigues Sousa, Pedro Henrique (REVISTA PARADIGMA, 2024)
Advertising plays an important role in consumer market, as it can awaken previously non-existent needs in the consumer and, due to its too much economic potential, has encouraged the creation and use of various engagement strategies. Some marketplace platforms store consumers’ data without proper consent and uses them for the development of advertising according to their behavior. Thus, the issue is based on the absence of regulation regarding such advertising strategy in the Brazilian legal system, since this conduct may violate the privacy of consumers, besides enabling a disproportionate advantage over other suppliers. It seeks to demonstrate what are the legal limits for the development of this practice, as well as to relate the Law of Consumer Relations to the Competition Law, since behavioral advertising unbalances the use of data allowing a non-egalitarian development of the trading system. Therefore, the methodological procedures used for this analysis consist of applied research, with a qualitative and hypothetical-deductive approach and descriptive objective, given to socioeconomic applicability. It is concluded, in view of this, that although behavioral advertising does not yet have a specific regulation in the Brazilian consumer microsystem, when the collection of data is not expressly authorized by consumers, this conduct can be considered abusive, based on Article 39 of the CDC, due to the violation of consumer privacy and the configuration of unfair competition.